Green Strategy to Develop Novel Drug-Containing Poly (ε-Caprolactone)-Chitosan-Silica Xerogel Hybrid Fibers for Biomedical Applications. (24th December 2020) - Zhou, Hua-Jian; Teng, Shu-Hua; Zhou, Yi-Bo; Qian, Hai-Sheng
Abstract : A facile and green method was explored to prepare the tetracycline hydrochloride- (TCH-) loaded poly ( ε -caprolactone)-chitosan-silica xerogel (PCL-CS-SiO2 ) hybrid fibers by using 90% acetic acid as a suitable solvent. The SEM results showed that those fibers exhibited a continuous, bead-free morphology, an average diameter of about 430 nm, and super-hydrophilicity (θ water ≈ 0 ° ). The presence of SiO2 was found to enhance the thermal stability of the hybrid fibers, and the actual content of SiO2 was obtained by the TG measurement. Moreover, SiO2 xerogel as an important bioceramic endowed the hybrid fibers with good drug release behavior and in vitro bioactivity, suggesting their potential use as novel drug carriers for bone tissue engineering. The present work is expected to offer a green strategy to develop novel, multifunctional hybrid materials.